The Impact of Cognitive Load on the Spatial Deployment of Visual Attention: Testing the Role of Interhemispheric Balance With Biparietal Transcranial Direct Current Stimulation - Paladini, Rebecca E.; Wieland, Fluri A. M.; Naert, Lien; Bonato, Mario; Mosimann, Urs P.; Nef, Tobias; Müri, René M.; Nyffeler, Thomas; Cazzoli, Dario (Frontiers in Neuroscience, 2020)
In healthy individuals, increasing cognitive load induces an asymmetric deployment of visuospatial attention, which favors the right visual space. To date, the neural mechanisms of this left/right attentional asymmetry are poorly understood. The aim of the present study was thus to investigate whether a left/right asymmetry under high cognitive load is due to a shift in the interhemispheric balance between the left and right posterior parietal cortices (PPCs), favoring the left PPC. To this end, healthy participants completed a visuospatial attention detection task under low and high cognitive load, whilst undergoing biparietal transcranial direct current stimulation (tDCS). Three different tDCS conditions were applied in a within-subjects design: sham, anodal left/cathodal right, and cathodal left/anodal right stimulation. The results revealed a left/right attentional asymmetry under high cognitive load in the sham condition. This asymmetry disappeared during cathodal left/anodal right tDCS, yet was not influenced by anodal left/cathodal right tDCS. There were no left/right asymmetries under low cognitive load in any of the conditions. Overall, these findings demonstrate that attentional asymmetries under high cognitive load can be modulated in a polarity-specific fashion by means of tDCS. They thus support the assumption that load-related asymmetries in visuospatial attention are influenced by interhemispheric balance mechanisms between the left and right PPCs.